The way things work - Macaulay, David (Boston : Houghton Mifflin, 1988)
Text and numerous detailed illustrations introduce and explain the scientific principles and workings of hundreds of machines including a lawn sprinkler, pneumatic drill, electric guitar, and a smoke detector.
Includes index.
Keywords: Technology -- Popular works; Technology